Mathematical Knowledge in Contexts of Solidary Economic Enterprises - de Moura, Carla Saturnina Ramos; Costa, Erilva Machado; Simão, Rosimeire Morais Cardeal; Ramos, Jorge Luis Cavalcanti; Yamamoto, Sandra Mari; Nunes, Xirley Pereira (International Journal of Advanced Engineering Research and Science, 2020)
This study aims to identify mathematical situations in practices of Solidary Economic Enterprises - EES, as well as to describe the performance of the ethnomatematic program in research with EES. The study consists of a bibliographic review with a qualitative approach, in which articles were selected in the CAPES Journal Portal. Thus, we conclude that there are situations in EES in which mathematical knowledge is used, such as: the understanding of spreadsheets; the organization of tables for production control; the calculation of materials needed for production and the understanding of mathematical operations used for budgeting the enterprise. It was identified that members did not understand these mathematical contents, and pedagogical interventions were carried out that were guided by the Ethnomathematics program, contemplating activities that valued the context of each enterprise and the previous knowledge of the members..